Guiding Principles for Management of Forested, Agricultural, and Urban Watersheds. (April 2015) - Edwards, Pamela J.; Schoonover, Jon E.; Williard, Karl W. J.
Abstract Human actions must be well planned and include consideration of their potential influences on water and aquatic ecosystems – such consideration is the foundation of watershed management. Watersheds are the ideal land unit for managing and protecting water resources and aquatic health because watersheds integrate the physical, biological and chemical processes within their boundaries. Managed forested watersheds tend to have more natural watershed functions and better water quality than other land uses. Land uses with greater amounts of soil disturbance and permanent reductions in infiltration, such as in agricultural or urban/developed settings, usually have greater undesirable hydrologic alterations and poorer water quality. Nonpoint source pollutants resulting from many forestry, agricultural, and urban activities are controlled by techniques and tools known as best management practices (BMPs). Best management practices are applied by watershed managers to large‐scale landscapes, but they also are applicable to the lives of ordinary citizens. Basic BMP principles, such as controlling the amounts and duration of soil disturbance during construction around the home, applying chemicals to lawns or gardens only at needed rates and during suitable times, and incorporating techniques to encourage infiltration of rooftop and driveway runoff are important actions that anyone can take to help protect watershed functions, water quality, and aquatic health.